Experimental characterization of adobe vaults strengthened with a TRM-based compatible composite - Sadeghi, Neda H. (2022)
This paper deals with the structural behaviour and strengthening of adobe vaults representative from historical buildings of the city of Yazd, Iran. Eight destructive tests were performed on 1:3 scaled adobe vault models by loading them at 30% of the span in loading-unloading cycles of increasing vertical displacement. The models were tested considering both unstrengthened and strengthened conditions, where the strengthening consisted of an externally bonded low-cost textile reinforced mortar (LC-TRM) composed of a low-cost fiber-glass mesh embedded in earth-based mortar. Three different strengthening strategies were evaluated, namely by testing undamaged models strengthened at the extrados, undamaged models strengthened at the intrados and repaired models strengthened at the intrados. The experimental results show that the adopted LC-TRM composite improves the structural behavior of adobe vaults, by increasing substantially their load-bearing capacity and by changing the failure mechanism to more ductile ones.